Ibn al-Muqaffa’s Pride in his - Puig Montada, Josep (Anales del Seminario de Historia de la Filosofía, 2007)
’Abd Allâh Ibn al-Muqaffa’ (724-759) is known mainly as the translator of the Kalila wa-Dimna, a collection of tales, that he translated from Pahlavi (Middle Persian) into Arabic. Ibn al-Muqaffa’ was of Iranian ancestry and was proud of the Sassanian legacy. He was self-confident of the rational primacy of the Zoroastrian religion over the Arabic culture that at that time consisted of the Koran and poetry. In the article I point to the rational values found in the comments of Ibn al-Muqaffaÿ as related to the Zoroastrian legacy.